God in the Cross and Human Ethic in Rituals: On the Promotion of Social Cooperation and Philosophlical Construction by Christianity and Confucianism from the Perspective of Sacrifice System - PENG, Rui (Journal of Research for Christianity in China (JRCC), 2025)
This paper briefly analyzes how Christianity and Confucianism inherited and developed their respective early traditional sacrifice system, and how to put forward their own philosophy thoughts and how to promote their social cooperation based on those inheritances and developments. The core relationship between human and God, demonstrated in the sacrifice system from Old Testament, is “love the Lord your God”, which focused on Jehovah; and the core relationship between human and gods in the early Chinese sacrifice system is “respect ghosts”, which referred to the polytheism. Both of Christianity and Confucianism, not only inherited, but re-explained, reshaped and transformed their respective original worship tradition. Especially, to Christianity, New Testament is the inheritance, re-explanation and replacement for Old Testament; and to Confucianism, represented by Confucius, reshaped and reconstructed the old worship system by “kinship love” and human relationship ethic. In this sense, the core characters of Christianity are the sacrifice of Jesus Christ on the cross and the doctrine of “Trinity”; and the key symbols of Confucianism are ancestor worship and heaven worship, the “kinship love” and human relationship ethic. Moreover, both of Christianity’s and Confucianism’s inheritance, re-explanation, reconstruction to their own traditional system, have greatly promoted the social cooperation, so as to realize Pareto Optimality at that time, and then they respectively laid the foundations for their later social tendency.
Keywords: Sacrifice System, Cross, God, Ritual, Ethic, Social Cooperation